The Effect of Kilovoltage and Milliampere-Second Parameters on CT Number: Study Phantom Quality Control CT Scan - Muhammad Irsal; Aulia Narindra Mukhtar; Guntur Winarno; Gando Sari (Politeknik Kesehatan Kemenkes Jakarta II, 2022)
CT number is one of the indicators in determining the diagnosis of disease, so it is necessary to ensure the level of accuracy. The aim is to determine the parameters of kilovoltage and tube current to the CT value. Descriptive quantitative analytic research method with previously tested linearity and the suitability of the CT number. Furthermore, the variation of kilovoltage: 80kVp, 100kVp, 140kVp and the tube current value is 192mAs. After that, the tube current variation was continued: 80mAs, 100mAs, 140mAs and the voltage value was 120kVp. Phantom image results were analyzed using radiant viewer software with a region of interest (ROI) size of 5mm. Then analyze the correlation coefficient to determine the degree of relationship between the kilovoltage and milliampere-second parameters to the CT number. The results of the linearity test and the suitability of the CT number value were within the tolerance limit. For variations in kilovoltage to CT number , the correlation coefficient values ​​are water R2=0.09, fat R2=1, soft tissue R2=0.9, bone R2=0.7. As for the milliampere-second variation of the CT number , the correlation coefficient values ​​are: water R2=0.7, fat R2=0.8 , soft tissue R2=1, bone R2=0.7.